Fractalkine in human inflammatory cardiomyopathy. Issue 9 (25th February 2011) - Escher, F; Vetter, R; Kühl, U; Westermann, D; Schultheiss, H-P; Tschöpe, C
Abstract : Background: Cardiac inflammation is important for the prognosis of patients with inflammatory cardiomyopathy (CMi), but the mechanisms leading to it are not fully elucidated. Objective: To study the role of fractalkine (CX3CL1) in chemotactic and adhesive properties of peripheral blood mononuclear cells (PBMCs) in patients with CMi. Methods and results: Patients with enterovirus (EV)-positive CMi, patients with virus-negative CMi, patients with parvovirus B19 (B19) genomes with low intramyocardial inflammation and patients without cardiac inflammation and viral infection in the endomyocardial biopsy (EMB) were enrolled (n=10/group). The expression of CX3CL1 and monocyte chemoattractant protein (MCP-1) in EMBs was significantly increased in EV-positive and virus-negative patients with CMi in contrast to controls and B19-positive patients (EV+ vs controls: CX3CL1-area fraction (AF) % 0.078±0.012 vs 0.009±0.003 p<0.05; MCP-1-AF % 0.093±0.023 vs 0.011±0.009). The receptor (CX3CR1)-mediated chemotaxis was increased twofold in PBMCs in comparison with those of controls. The MCP-1 secretion was 3.1-fold higher in PBMCs from EV-positive patients compared with controls, and this elevation was further increased by CX3CL1 in EV-positive patients. No significant CX3CL1-mediated MCP-1 increase was seen in PBMCs from healthy controls. Moreover, spontaneously beating neonatal rat cardiomyocytes exposed to CX3CL1 exhibited an attenuated positive chronotropic response to β-adrenergic stimulation with isoproterenol. Conclusion: The cardiac and plasma CX3CL1/CX3CR1 system is upregulated in CMi and this affects the functional potential of PBMCs. Moreover, a direct cardiodepressive effect of CX3CL1 in cardiac tissue was demonstrated since neonatal cardiomyocytes exhibited an attenuated positive chronotropic response to β-adrenergic stimulation.